Interactive effect between ATPase-related genes and early-life tobacco smoke exposure on bronchial hyper-responsiveness detected in asthma-ascertained families. Issue 3 (3rd October 2018) - Dizier, Marie-Hélène; Margaritte-Jeannin, Patricia; Pain, Lucile; Sarnowski, Chloé; Brossard, Myriam; Mohamdi, Hamida; Lavielle, Nolwenn; Babron, Marie-Claude C; Just, Jocelyne; Lathrop, Mark; Laprise, Catherine; Bouzigon, Emmanuelle; et al.
Abstract : Background: A positional cloning study of bronchial hyper-responsiveness (BHR) at the 17p11 locus in the French Epidemiological study on the Genetics and Environment of Asthma (EGEA) families showed significant interaction between early-life environmental tobacco smoke (ETS) exposure and genetic variants located in DNAH9 . This gene encodes the heavy chain subunit of axonemal dynein, which is involved with ATP in the motile cilia function. Our goal was to identify genetic variants at other genes interacting with ETS in BHR by investigating all genes belonging to the ' ATP-binding ' and ' ATPase activity ' pathways which include DNAH9, are targets of cigarette smoke and play a crucial role in the airway inflammation. Methods: Family-based interaction tests between ETS-exposed and unexposed BHR siblings were conducted in 388 EGEA families. Twenty single-nucleotide polymorphisms (SNP) showing interaction signals (p ≤ 5.10 −3 ) were tested in the 253 Saguenay-Lac-Saint-Jean (SLSJ) families. Results: One of these SNPs was significantly replicated for interaction with ETS in SLSJ families (p=0.003). Another SNP reached the significance threshold after correction for multiple testing in the combined analysis of the two samples (p=10 −5 ). Results were confirmed using both a robust log-linear test and a gene-based interaction test. Conclusion: The SNPs showing interaction with ETS belong to the ATP8A1 and ABCA1 genes, which play a role in the maintenance of asymmetry and homeostasis of lung membrane lipids.